The Prospect of Legalizing Casinos with Strict Regulations as a Strategy for Optimizing State Revenue and Social Control in Indonesia - Anisa (Journal of International Multidisciplinary Research, 2025)
The discourse on casino legalization in Indonesia arises as a response to the widespread illegal gambling that remains difficult to eradicate despite being prohibited under the Criminal Code (KUHP), Law No. 7 of 1974, and the Electronic Information and Transactions Law (ITE). The gap between legal norms (das sollen) and social reality (das sein) shows that prohibition alone has not been effective. This research uses a qualitative method with a normative juridical approach based on legislation and a comparative approach, particularly examining Malaysia and Singapore, which have successfully managed casinos through strict regulations. The findings indicate that casino legalization in Indonesia could serve as an alternative fiscal policy, provided that clear regulations are established, ensuring economic benefits such as increased state revenue and effective control over illegal gambling, without undermining national morals and values.